TdP Incidence in Methoxamine-Sensitized Rabbit Model Is Reduced With Age but Not Influenced by Hypercholesterolemia - Nalos, Lukáš; Jarkovská, Dagmar; Švíglerová, Jitka; Süß, Annabell; Záleský, Jakub; Rajdl, Daniel; Krejčová, Milada; Kuncová, Jitka; Rosenberg, Josef; Štengl, Milan (Frontiers in Physiology, 2021)
Metabolic syndrome is associated with hypercholesterolemia, cardiac remodeling and increased susceptibility to ventricular arrhythmias. Effects of diet-induced hypercholesterolemia on susceptibility to Torsades de Pointes arrhythmias (TdP) together with potential indicators of arrhythmic risk were investigated in 3 experimental groups of Carlsson´s rabbit model: 1) young rabbits (YC, young control, age 12-16 weeks), older rabbits (AC, adult control, age 20-24 weeks) and older age-matched cholesterol-fed rabbits (CH, cholesterol, age 20-24 weeks). TdP was induced by α-adrenergic stimulation by methoxamine and IKr block in 83% of YC rabbits, 18% of AC rabbits and 21% of CH rabbits. High incidence of TdP was associated with high incidence of single (SEB) and multiple ectopic beats (MEB), but the QTc prolongation and short-term variability (STV) were similar in all 3 groups. In TdP-susceptible rabbits, STV was significantly higher compared to arrhythmia-free rabbits but not to rabbits with other than TdP arrhythmias (SEB, MEB). Amplitude-aware permutation entropy analysis of baseline ECG could identify arrhythmia-resistant animals with high sensitivity and specificity. The data indicate that the TdP susceptibility in methoxamine-sensitized rabbits is affected by the age of rabbits but probably not by hypercholesterolemia. Entropy analysis could potentially stratify the arrhythmic risk and identify the low risk individuals.